1980
DOI: 10.1016/0304-3959(80)90079-2
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social aspects of chronic pain in spinal cord injury

Abstract: The relationship between persistent pain in spinal cord injury and medical-descriptive, demographic, psychological and familial-social data was studied. Multiple linear regression and discriminant analysis were used to predict (1) presence or absence of pain; (2) severity of pain; (3) time post-injury onset of pain; (4) whether or not pain interfered with activities of daily living. The best combinations of predictor variables accounted for only 15 and 19% of the dependent measures pain vs. no-pain and onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
2
4

Year Published

1986
1986
2007
2007

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(74 citation statements)
references
References 7 publications
5
63
2
4
Order By: Relevance
“…Except for the higher prevalence of musculoskeletal pain at 2 weeks, our ®ndings are consistent with the studies by Summers et al 14 and Richards et al 15 Both of these studies failed to ®nd any relationship between Figure 4 Percentage of people reporting the presence of neuropathic below level pain in each group at each interval up to 12 months following SCI Surgery and pain following SCI P Sved et al the presence of pain and surgical intervention. However, in contrast with the present study, neither of these studies assessed patients within the ®rst year following their injury and neither study distinguished di erent types of SCI pain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Except for the higher prevalence of musculoskeletal pain at 2 weeks, our ®ndings are consistent with the studies by Summers et al 14 and Richards et al 15 Both of these studies failed to ®nd any relationship between Figure 4 Percentage of people reporting the presence of neuropathic below level pain in each group at each interval up to 12 months following SCI Surgery and pain following SCI P Sved et al the presence of pain and surgical intervention. However, in contrast with the present study, neither of these studies assessed patients within the ®rst year following their injury and neither study distinguished di erent types of SCI pain.…”
Section: Discussionsupporting
confidence: 90%
“…The authors of these studies have concluded that psychosocial factors rather than physiological factors are more closely associated with the experience of pain. 14,15 It is also not clear whether the level of cord lesion is a signi®cant factor in the development of SCI pain. It has been reported that cervical, 1 thoracolumbar 16 and conus medullaris and cauda equina 10,17,18 injuries are most likely to be associated with the presence of pain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of SCI family research comprises statistical summaries on the effect of SCI trauma on marital stability (Crewe et al, 1979;DeVivo and Fine, 1985;El Ghatit and Hansen, 1975;1976) and descriptive accounts (Mailick, 1979;Rohrer et al, 1980;Weller and Miller, 1977a;1977b) or case observations (Cleveland, 1979;White, 1983) of SCI families undergoing acute rehabilitation. In a study of SCI treatment outcome Richards et al (1980) report that SCI subjects who had more pain related disability were members of families with greater psychosocial dysfunction as assessed by staff ratings. Unfortunately, in this study as in others (Litman, 1962) the use of nonstandardised measures of family process compromises the validity and generalisability of the findings.…”
Section: Introductionmentioning
confidence: 99%